Social Welfare Handling in Underdeveloped Region A Case Study in Garut Regency - Kissumi Diyanayati (Jurnal Penelitian Kesejahteraan Sosial, 2014)
According to the Ministry of Underdeveloped Regions Affairs data, Garut Regency is one out of 183 underdeveloped regencies in Indonesia. The development program on the underdeveloped regions is focused on the development acceleration in the regions which its social, culture, economy, local fund, accessible, and infrastructure providing are still underdeveloped. Lifting underdeveloped regions needs a commitment among government, private sector, and community. The Ministry of Social Affairs, as work contract between Minister of Social Affairs and President, has special task to lift 50underdeveloped regencies, one of them is Garut Regency. The approach used in this research is evaluative-descriptive technique, and done to know the role and benefit of the program on lifting underdeveloped regency, especially Garut Regency. Data resources are fifteen informants of local social agency, social guide, and beneficiary. Data are gathered through interview, observation,and documentary analysis. Data are analyzed through qualitative technique. The significant result of the program from The Ministry of Social Affairs are poverty prevention through joint entrepreneurship (Kube), slum renovation (RLTH), socialharmony, and family hope program. For the sake of the social problem handling to be more optimum, it is recommended that the Ministry of Social Affairs build coordination and synergy among UKE I program. Local government should immediately verify social welfare problems (PMKS) to be used as basic data on social problem handling.